Is there a Theory – Practice – Ethics gap? A Patient Safety Case Study - Mortell, Manfred (Elsevier Ltd., 2019)
This exposé employs a case study to illuminate an ongoing medical dilemma which places a patient’s safety at risk. The medical dilemma is one of non-compliance by healthcare professionals and is associated with correct patient identification. Typically, the healthcare academics declare that when clinical practice is inadequate, a “theory-practice gap” is usually responsible. Within this paradigm there is often a gap between theoretical knowledge and its application in practice. Most of the evidence relating to the non-integration of theory and practice makes the assumption that environmental factors are responsible and will affect learning and practice outcomes, hence the “gap”. However, it is the author's belief, that to “bridge the gap” between theory and practice an additional component must be considered, called “Ethics”. In order to effectively implement practices, such as identifying a patient correctly, the user must deem these practices to be important and relevant to provide safe patient care in their role as healthcare providers. This introduces a new concept which the author refers to as the “theory-practice-ethics gap” and must be considered when reviewing some of the unacceptable outcomes in healthcare practice, such as wrong patient identification.